Anti‐Black Racism as a Chronic Condition. (26th April 2022) - Sederstrom, Nneka; Lasege, Tamika
Abstract: Because America has a foundation of anti‐Black racism, being born Black in this nation yields an identity that breeds the consequences of a chronic condition. This article highlights several ways in which medicine and clinical ethics, despite the former's emphasis on doing no harm and the latter's emphasis on nonmaleficence, fail to address or acknowledge some of the key ways in which physicians can—and do—harm patients of color. To understand harm in a way that can provide real substance for ethical standards in the practice of medicine, physicians need to think about how treatment decisions are constrained by a patient's race. The color of one's skin can and does negatively affect the quality of a person's diagnosis, promoted care plan, and prognosis. Yet racism in medicine and bioethics persist—because a racist system serves the interests of the dominant caste, White people. As correctives to this system, the authors propose several antiracist commitments physicians or ethicists can make.